OPTIMIZATION OF TRAFFIC CONGESTION MANAGEMENT BY THE TURJAGWALI UNIT TO IMPROVE THE PERFORMANCE OF TRAFFIC UNITS IN ORDER TO REALIZE KAMSELTIBCAR LALU IN THE WONOSOBO POLICE JURISDICTION - Muhamad Rizqi Yudha Pratama (Advances in Police Science Research Journal, 2022)
Traffic jams that occur in cities in Indonesia are still a problem that cannot be resolved. The dynamics of society become a cause of traffic conditions are always changing in accordance with the development of community mobility in Indonesia. The National Police of the Republic of Indonesia through the Turjagwali Unit of the Wonosobo Police Traffic Unit has carried out traffic congestion management in the wonosobo police jurisdiction. However, in its implementation is still considered less than optimal because there are still traffic jams that occur in the wonosobo police jurisdiction. This research aims to find out the implementation of traffic congestion management by the Turjagwali Unit of the Wonosobo Police Traffic Unit which is seen in terms of management and organizational resources, supporting factors and obstacles from the implementation and strives to optimize the implementation of traffic congestion management that occurs in Wonosobo Regency. The analysis knives used include management theory, organizational resource theory, as well as SWOT analysis. The concepts used are the concept of traffic, the concept of smooth traffic, the concept of traffic congestion, the concept of management, and the concept of performance. The approach taken is qualitative short with analytical descriptive. Data collection methods include interviews, observations, and document studies. The results of the study found that the implementation of traffic congestion management by the Turjagwali Unit of the Wonosobo Police Traffic Unit has not been optimal by looking at the management and resources of existing organizations. In the end, researchers found the problems that occurred and could answer ways to optimize traffic congestion management based on laws, police regulations, and operational standards of applicable procedures.